Front Matter - Widodo Widodo (Universitas Muhammadiyah Yogyakarta, 2020)
AGRARIS is a periodical of scientific journals on Agribusiness and Rural Development. AGRARIS is published twice a year (January-June, and July-December) by the Department of Agribusiness, Faculty of Agriculture, Universitas Muhammadiyah Yogyakarta in collaboration with Agribusiness Association of Indonesia (AAI). AGRARIS accredited “B” by Decree of The Indonesian Ministry of Research, Technology, and Higher Education (RISTEKDIKTI) No.51/E/KPT/2017 on 4th December 2017.